PENGARUH CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Zuhriyah Zuhriyah; Gusnardi Gusnardi; Hendripides Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine corporate governance that represented by institutional ownership, managerial ownership, the size of the independent commissioner, and size of the board of directors had an influence on company performance at manufacturing companies which is listing in Indonesia Stock Exchange for 2013 period until 2017. This study used quantitative descriptive with correlational design with the help of multiple regression. The data that used in this study was secondary data which was company’s annual report. The population of this study is all of the manufacturing companies amounting 146 companies with aim sample technique which have some criterias. The amount of sample in this study is 26 manufacturing companies. Simultaneously corporate governance had an influence on company performance at manufacturing companies which is listing in BEI for 2013 period until 2017 with contribution amounted 10,9%. Partially, institutional ownership had no influence on company performance, managerial ownership had no influence on company performance, the size of the independent commissioner had no influence on company performance, and size of the board of directors had an influence on company performance.Key Words: Corporate Governance, Company Performance